Hubungan Asupan Zat Besi, Vitamin C, dan Persen Lemak Tubuh dengan Kejadian Anemia pada Remaja Putri di Pondok Pesantren Askhabul Kahfi Kota Semarang: The Relationship Between Iron Intake, Vitamin C, and Body Fat Percentage with the Incidence of Anemia in Adolescent Girls at Askhabul Kahfi Islamic Boarding School Semarang City - Hardiansyah, Angga; Aulia, Elly Putri; Sugiyanti, Dina (Amerta Nutrition, 2024)
Background: Anemia is a medical condition that arises from a deficiency of certain nutrients and is commonly observed in both developed and developing countries. Deficiencies in essential nutrients, such as iron, folic acid, protein, and vitamin C, are frequent causes of anemia in adolescents. Additionally, other factors, including body fat percentage, may also contribute to the condition. Objectives: To analyze the relationship between iron intake, vitamin C intake, and body fat percentage among adolescent girls at Askhabul Kahfi Islamic Boarding School in Semarang City. Methods: This cross-sectional study involved 65 adolescent girls selected using proportionate stratified sampling. Iron and vitamin C intake data were collected through interviews using the SQ-FFQ. Body fat percentage was measured using the Omron HBF-212 BIA device, and anemia was diagnosed based on hemoglobin levels using the EasyTouch GCHb device. Bivariate analysis was conducted with the Gamma correlation test, and multivariate analysis used ordinal logistic regression. Results: Among the respondents, 33 (50.8%) had adequate iron intake, 35 (53.2%) had adequate vitamin C intake, 43 (66.2%) had normal body fat percentages, and 42 (64.6%) were not anemia. A significant relationship was found between iron intake (p-value = 0.010) and body fat percentage (p-value = 0.009) with anemia incidence. No significant relationship was found between vitamin C intake (p-value = 0.095) and anemia. Conclusions: Iron intake and body fat percentage are significantly relationship with anemia in adolescent girls, with iron intake being the most influential factor.